2019
DOI: 10.1111/cote.12440
|View full text |Cite
|
Sign up to set email alerts
|

Degradation studies of CI Reactive Blue 19 on biodegraded cellulosic fabrics via liquid chromatography‐photodiode array detection coupled to high resolution mass spectrometry

Abstract: When textile substrates biodegrade in landfills, the fate of textile colorants is unknown, and potentially poses an ecotoxic threat. In this study, we developed a systematic analytical method to evaluate the biodegradation of reactive dyes, the most common class of dye applied to cotton fabrics. The cotton fabrics were dyed with CI Reactive Blue 19 and biodegraded in soil in a laboratory‐controlled environment over intervals of 45 and 90 days. A dye isolation method using a low concentration of alkali (0.15% s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Therefore, to analyze reactive dyes and their hydrolysis and degradation products, it is necessary to break the glucose–dye bond. In earlier studies, it has been shown that in alkaline conditions, reactive dyes can be isolated from cotton fibers and become hydrolyzed by the cleavage of the glucose–dye linkage [19,20]. In addition to chemical treatment, enzymatic treatment relies on the action of cellulase enzymes, which can digest dye–cellulose linkages and release the dye from the fabric.…”
Section: Identification and Characterization Of Synthetic Dyes By Empmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, to analyze reactive dyes and their hydrolysis and degradation products, it is necessary to break the glucose–dye bond. In earlier studies, it has been shown that in alkaline conditions, reactive dyes can be isolated from cotton fibers and become hydrolyzed by the cleavage of the glucose–dye linkage [19,20]. In addition to chemical treatment, enzymatic treatment relies on the action of cellulase enzymes, which can digest dye–cellulose linkages and release the dye from the fabric.…”
Section: Identification and Characterization Of Synthetic Dyes By Empmentioning
confidence: 99%
“…Dye degradation is an indispensable part when using dyes for applications, and this phenomenon has attracted the attention of most dye researchers. Chromatography has been the most effective technique for separation dye mixtures, and it has been widely applied for characterizing dye degradation products [20,36–39]. According to Sinha et al., HPLC chromatography can help to observe the decolorization process, since the shift of major peak and the appearance of a new peak can be seen from the HPLC chromatogram, indicating the discoloration of dye into different intermediates [38].…”
Section: Identification and Characterization Of Synthetic Dyes By Empmentioning
confidence: 99%
See 3 more Smart Citations